Séamas de Barra, Aloys Fleischmann (2006) - McCarthy, Marie (Journal of the Society for Musicology in Ireland, 2007)
A review of Séamas de Barra, Aloys Fleischmann (Dublin: Field Day Publications, 2006) ISBN 0-946755-32-9, x + 190pp, €25.00/34.77